2002
DOI: 10.1073/pnas.152337399
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of monomeric human β-2-microglobulin reveals clues to its amyloidogenic properties

Abstract: Dissociation of human ␤-2-microglobulin (␤2m) from the heavy chain of the class I HLA complex is a critical first step in the formation of amyloid fibrils from this protein. As a consequence of renal failure, the concentration of circulating monomeric ␤2m increases, ultimately leading to deposition of the protein into amyloid fibrils and development of the disorder, dialysis-related amyloidosis. Here we present the crystal structure of a monomeric form of human ␤2m determined at 1.8-Å resolution that reveals r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
177
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 177 publications
(192 citation statements)
references
References 38 publications
(65 reference statements)
14
177
0
Order By: Relevance
“…On the contrary, some amyloidogenic proteins retain their native structures before undergoing conformational transition and eventual fibril formation (55). This group of proteins include prion (56), β2-microglobulin (β2m) (57,58), lysozyme (59,60), transthyretin (TTR) (61), and the variable region of immunoglobulin lightchain (VL) (62), which are responsible for mad cow disease (63), dialysis-related amyloidosis (64), hereditary systemic amyloidosis http://bmbreports.org BMB reports (65), senile systemic amyloidosis (61) and light-chain amyloidosis (62), respectively. In addition, apomyoglobin prepared by phase separation using the acid methylethylketone method (66) formed amyloid-like structures upon denaturation in 50 mM sodium borate, pH 9.0, at 65 o C, suggesting that amyloid fibril formation could be considered a generic phenomena of proteins as they experience misfolded structures (67,68).…”
Section: Various Amyloidogenic Proteinsmentioning
confidence: 99%
“…On the contrary, some amyloidogenic proteins retain their native structures before undergoing conformational transition and eventual fibril formation (55). This group of proteins include prion (56), β2-microglobulin (β2m) (57,58), lysozyme (59,60), transthyretin (TTR) (61), and the variable region of immunoglobulin lightchain (VL) (62), which are responsible for mad cow disease (63), dialysis-related amyloidosis (64), hereditary systemic amyloidosis http://bmbreports.org BMB reports (65), senile systemic amyloidosis (61) and light-chain amyloidosis (62), respectively. In addition, apomyoglobin prepared by phase separation using the acid methylethylketone method (66) formed amyloid-like structures upon denaturation in 50 mM sodium borate, pH 9.0, at 65 o C, suggesting that amyloid fibril formation could be considered a generic phenomena of proteins as they experience misfolded structures (67,68).…”
Section: Various Amyloidogenic Proteinsmentioning
confidence: 99%
“…1) (12). Several lines of evidence, including detailed folding studies and mutagenesis experiments on β2m, have suggested that cis-to-trans isomerization of Pro32 serves as a trigger to misfolding and subsequent aggregation (6,13).…”
mentioning
confidence: 99%
“…b2m is expressed on the surface of nearly all nucleated cells and it adopts an immunoglobulin fold, made up of a seven-stranded b-sandwich linked by a disulphide bridge (Fig. 4E, left part) [88,89]. Although the increased concentration of b2m is a decisive factor in causing DRA, it is not sufficient by itself.…”
Section: B2-microglobulin and Dialysis-related Amyloidosismentioning
confidence: 99%